Computational and Pharmacological Evaluation of Carveol for Antidiabetic Potential - Ahmed, Muhammad Shabir; Khan, Arif-ullah; Kury, Lina Tariq Al; Shah, Fawad Ali (Frontiers in Pharmacology, 2020)
Background Carveol is a natural drug product present in the essential oils of orange peel, dill, and caraway seeds. The seed oil of Carum Carvi has been reported to be antioxidant, anti-inflammatory, anti-hyperlipidemic, antidiabetic, and hepatoprotective. Methods The antidiabetic potential of carveol was investigated by employing in-vitro, in-vivo, and in-silico approaches. Moreover, alpha-amylase inhibitory assay and an alloxan-induced diabetes model were used for in-vitro and in-vivo analysis, respectively. Results Carveol showed its maximum energy values (≥ -7 Kcal/mol) against sodium-glucose co-transporter, aldose reductase, and sucrose-isomaltase intestinal, whereas it exhibited intermediate energy values (≥ -6 Kcal/mol) against C-alpha glucosidase, glycogen synthase kinases-3β, fructose-1,6-bisphosphatase, phosphoenolpyruvate carboxykinase, and other targets according to in-silico analysis. Similarly, carveol showed lower energy values (≥ 6.4 Kcal/mol) against phosphoenolpyruvate carboxykinase and glycogen synthase kinase-3β. The in-vitro assay demonstrated that carveol inhibits alpha-amylase activity concentration-dependently. Carveol attenuated the in-vivo alloxan-induced (1055.8 µMol/Kg) blood glucose level in a dose- and time-dependent manner (days 1, 3, 6, 9, and 12), compared to the diabetic control group, and further, these results are comparable with the metformin positive control group. Carveol at 394.1 µMol/Kg improved oral glucose tolerance overload in rats compared to the hyperglycemic diabetic control group. Moreover, carveol also attenuated the glycosylated hemoglobin level along with mediating anti-hyperlipidemic and hepatoprotective effects in alloxan-induced diabetic animals. Conclusions This study reveals that carveol exhibited binding affinity against different targets involved in diabetes and has antidiabetic, anti-hyperlipidemic, and hepatoprotective actions.